Fenomena Intrusi Air Laut di Daerah Pesisir Hunuth, Kecamatan Teluk Ambon, Kota Ambon, Maluku - Kololu, Micky (Journal of Science, Technology, and Visual Culture, 2023)
One of the research areas to determine the phenomenon of seawater intrusion through analysis of the physical and chemical characteristics of groundwater is in the Coastal area of ​​Hunuth Village, Teluk Ambon District, Ambon City, Maluku. The coastal community of Hunuth Village utilizes groundwater to meet their daily water needs. However, due to the existence of residential areas close to the coast, the groundwater in this area has been polluted or intruded by sea water.The results showed that groundwater with high pH values ​​was shown in areas far from the shoreline (northern part of the study area), while high TDS, salinity and DHL values ​​were generally found in groundwater samples close to the shoreline. The groundwater facies in the study area show the types of Ca-HCO3 (calcium and bicarbonate), types of Na-HCO3 (sodium and bicarbonate), and types of Na-Cl (sodium and chloride). Areas close to the shoreline have experienced seawater intrusion as indicated by DHL values ​​> 229.25 mho/cm, Cl/HCO3 ratio values ​​which are generally > 2.80 meq/l, and groundwater facies with the type of Na-Cl (sodium and sodium chloride). Therefore, it is necessary to treat water before it is used as drinking water, buy bottled drinking water or use the services of a water company for polluted wells, and build a dam in the northern part of the study area which has a flat topography. trees to retain water, so that fresh water can easily push salt water into groundwater aquifers in the study area.